The Organization of the Islamic Conference (OIC): Nations in Search of Unity - Al-Roubale, Amer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Organization of the Islamic Conference (OIC): Nations in Search of Unity